2019
DOI: 10.1111/jocn.14731
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transtheoretical model‐based intervention on the self‐management of patients with an ostomy: A randomised controlled trial

Abstract: Aims and objectives To determine the effect of a transtheoretical model (TTM)‐based intervention on patients with an ostomy and provide patient‐centred, accessible assistance and dynamic education to improve patient self‐management. Background Proper self‐management may promote the rehabilitation of patients with an ostomy. TTM‐based interventions have resulted in positive health behavioural changes. Design Randomised controlled trial performed according to the CONSORT guidelines. Subject and setting The sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 43 publications
2
42
0
2
Order By: Relevance
“…Information and autonomy might be interrelated, and it is not surprising that they both were associated with self‐care maintenance and monitoring. In fact, prior studies have already shown that educational programmes during the pre‐ and postoperative phases improve ostomy self‐care (Faury, Koleck, Foucaud, M’Bailara, & Quintard, 2017; Seo, 2019; Wen et al., 2019). People who are autonomous in their care are implicitly more likely to perform self‐care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information and autonomy might be interrelated, and it is not surprising that they both were associated with self‐care maintenance and monitoring. In fact, prior studies have already shown that educational programmes during the pre‐ and postoperative phases improve ostomy self‐care (Faury, Koleck, Foucaud, M’Bailara, & Quintard, 2017; Seo, 2019; Wen et al., 2019). People who are autonomous in their care are implicitly more likely to perform self‐care.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a permanent ostomy can live with it even for several years (Krouse et al., 2016) if we consider the ostomies as the result of colorectal (Sun et al., 2013) or bladder cancer (Jensen, Kiesbye, Soendergaard, Jensen, & Kristensen, 2017), which have a 5‐year survival rate of between 40% and 65% (Liu et al., 2016; Siegel et al, 2017). Therefore, an ostomy can lead to complex and lifelong consequences for patients (Villa, Mannarini, et al, 2019; Wen et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates that individuals fail to engage in regular physical activity due to low self-efficacy, low perceived benefits, and high perceived barriers (Wen et al, 2018). A number of factors are responsible for behavior changes in physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Patients’ individual needs, preferences for care, and goals must be considered for optimum outcomes (Richards et al, 2007). A systematic review concluded that tailored interventions, a patient-centered approach in which information delivery is customized to match patient’s characteristics, were nearly 50% more effective than standard interventions in promoting health behavior outcomes (Wen et al, 2018).…”
mentioning
confidence: 99%
“…Self-efficacy refers to the belief that an individual can effectively initiate the necessary activities and perform the necessary behaviours (Bandura, 1997). A study conducted by Wen et al (2019) found that self-management behaviour changes facilitated a positive adaptation to the chronic condition of those living with a stoma. Therefore, an effective tool is needed to accurately measure self-management behaviours and to elucidate its role in the self-management of people living with a stoma after RC and IC.…”
Section: Introductionmentioning
confidence: 99%